How Women Workers Act Economically - Holik, Abdul; Nuraini, Nuraini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
This research tries to find several factors triggering female workers to shop. It involved 70 respondents that are active female workers. The method use here is OLS (Ordinary Least Square) that makes us easy to explain relational framework of independent variables toward dependent variable. Based on the result, we find that decision to shop is affected by only two independent variables: decision-making and external locus of control. The rest of independent variables do not have effect at all. This finding proves that the tendency of female workers to shop is constituted by their own attitude and the external environment that they cannot handle.